Microbial Responses to Simulated Salinization and Desalinization in the Sediments of the Qinghai–Tibetan Lakes - Huang, Jianrong; Yang, Jian; Jiang, Hongchen; Wu, Geng; Liu, Wen; Wang, Beichen; Xiao, Haiyi; Han, Jibin (Frontiers in Microbiology, 2020)
Uncovering microbial response to salinization or desalinization is of great importance to understanding of the influence of global climate change on lacustrine microbial ecology. In this study, to simulate salinization and desalinization, sediments from Erhai Lake (salinity 0.3–0.8 g/L) and Chaka Lake (salinity 299.3–350.7 g/L) on the Qinghai-Tibetan Plateau were transplanted into different lakes with a range of salinity of 0.3–299.3 g/L, followed by in-situ incubation for 50 days and subsequent geochemical and microbial analyses. Desalinization was faster than salinization in the transplanted sediments. The salinity of the transplanted sediment increased and decreased in the salinization and desalinization simulation experiments, respectively. The TOC contents of the transplanted sediments were lower than that of their undisturbed counterparts in the salinization experiments, while they had a strong negative linear relationship with salinity in the desalinization experiments. Microbial diversity decreased in response to salinization and desalinization, and microbial community dissimilarity significantly (P < 0.01) increased with salinity differences between the transplanted sediments and their undisturbed counterparts. Microbial groups belonging to Gammaproteobacteria and Actinobacteria became abundant in salinization while Bacteroidetes and Chloroflexi became dominant in desalinization. Among the predicted microbial functions, hydrogenotrophic methanogenesis, methanogenesis through CO2 reduction with H2, nitrate/nitrogen respiration and nitrification increased in salinization; in desalinization, enhancement was observed for respiration of sulfur compounds, sulfate respiration, sulfur respiration, thiosulfate respiration, hydrocarbon degradation, chemoheterotrophy and fermentation, while depressing was found for aerobic ammonia oxidation, nitrate/nitrogen respiration, nitrification, nitrite respiration, manganese oxidation, aerobic chemoheterotrophy and phototrophy. Such microbial variations could be explained by changes of transplantation, salinity and covarying variables. In summary, salinization and desalinization had profound influence on the geochemistry, microbial community and function in lakes.